Transition and coherence in intellectual property law essays in honour of Annette Kur - Bruun, Niklas 1950-; Dinwoodie, Graeme B. 1966-; Levin, Marianne 1942-; Ohly, Ansgar 1965- (Cambridge University Press, 2020)
The nature and content of intellectual property (IP) law, which is heavily contingent on the state of technology and on social and market developments, has always been subject to ongoing transitions. How those transitions are effected and the shape they take is crucial to the ability of IP to achieve its stated goals and provide the necessary climate for investment in creativity, innovation and brand differentiation. Yet the need for change can run headlong into a desire for coherence. A search for coherence tests the limits of the concept of "intellectual property," is imperiled by overlaps between different IP regimes, and calls for a unifying normative theme. This volume assembles contributors from across IP and the globe to explore these questions, including whether coherence is desirable. It should be read by anyone interested in understanding the conceptual underpinnings of one of the most important and dynamic areas of the law
Title from publisher's bibliographic system (viewed on 05 Jan 2021)
Transitional provisions in intellectual property legislation / Richard Arnold -- Judicial creativity and transitions in EU IP law / Lionel Bently -- Before and after designers guild : another look at appellate deference in New Zealand's copyright law / Graeme W. Austin -- EU design law : transitioning towards coherence? 15 Years of EU Design Law : transitioning towards coherence? 15 years of National case law / Estelle Derclaye -- Copyright and the CJEU : some structural deficits as seen from a German perspective / Thomas Dreier -- Global intellectual property : transition and coherence through rules of interpretation / Susy Frankel -- Article 20 of the TRIPS Agreement : up in smoke? / Daniel J. Gervais -- Implementing international obligations at the national level / Sam Ricketson -- Multiple and overlapping transitions in IP / Marco Ricolfi -- Transition and continuity in the private international law of intellectual property / Christian Heinze --
- From Nintendo Wii to perfumes, driving a BMW car : a tale of transition to the wrong kind of coherence / Paul Torremans -- Transition through automation / Henning Grosse Ruse-Khan -- Eye, robot : artificial intelligence and trade mark registers / Dev S. Gangjee -- Patent protection of inventions involving artificial intelligence / Stefan Luginbuehl -- Automated profiling in new media and entertainment markets : what to protect, and how? / Megan Richardson -- The (lack of) coherence of data ownership with the intellectual property system / Josef Drexl -- The threefold fictitiousness of intellectual property / Alexander Peukert -- An intellectual property structural engineer extraordinaire and her lifelong quest for coherence / Peter K. Yu -- Open yet secret : trading of tangible goods and trade secrets / Nari Lee -- From Smorgasbord to new Nordic Cuisine : EU harmonization of trade secrets protection in the Nordic countries / Jens Schovsbo --
- Trade mark rights and parallel imports vis-à-vis the never-ending evolution of the behavior of firms : transition and coherence put to a test / Vincenzo Di Cataldo -- Legal concept of "exhaustion" : exhausted? / Reto M. Hilty -- Building coherence in technological transitions : putting exploitation at the core of intellectual property / Severine Dussollier -- 'Accessory Exhaustion' : and use of a work as a work / Ole-Andreas Rognstad -- Intellectual property in transition : the several sides of overlapping copyright and trademark protection / Irene Calboli and Jane C. Ginsburg -- Cultural heritage and the public domain : what the US's Myriad and Mayo can teach Oslo's Angry Boy / Rochelle C. Dreyfuss -- Public order in the light of aesthetic theory : the copyright/trademark interface after Vigeland / Martin R.S.F Senftleben -- Separability as channeling : a cautionary tale / Mark P. McKenna --
- Novelty, idea, or new meaning as criteria for copyright protection? : transitions in Swedish design law / Jan Rosén -- Examining functionality / Mark D. Janis -- Substantial value and the concept of shape / Antoon A. Quaedvlieg -- Copyright and patents on software : the UPC's answer to an old problem of intellectual property overlaps / Axel Metzger -- Chopping off Hydra's heads : spare parts in EU design and trade mark law / Anna Tischner -- Geographical indications as intellectual property rights : beyond transition and coherence? / Roland Knaak -- Presence or absence of coherence in trade identity protection in the European Union / Alexander von Mühlendahl -- Virtue ethics and private law : a sketch / Marcus Norrgard -- Closing the gap : how EU law constrains national rules against imitation? / Martin Husovec -- European Union law and Slavish imitation : an 'update' in honour of Annette Kur / Matthias Leistner --
Keywords: Kur, Annette; Agreement on Trade-Related Aspects of Intellectual Property Rights / (1994 April 15); Intellectual property / European Union countries; Intellectual property (International law); Festschrift